Phenotypic stability of the human MG‐63 osteoblastic cell line at different passages. (27th December 2018) - Staehlke, Susanne; Rebl, Henrike; Nebe, Barbara
Abstract: One of the most popular cell lines in osteogenesis studies is the human osteoblastic line MG‐63. For cell biological investigation, it is important that the cells remain stable in their phenotype over several passages in cell culture. MG‐63 cells can be used to provide fundamental insights into cell‐–material interaction. The aim of this study is to present a systematic characterization of the physiological behavior of MG‐63 cells in the range of passages 5–30. Significant cell physiology processes during the first 24 h, including cell morphology, availability of adhesion receptors, cell cycle phases, as well as the expression of the signaling proteins Akt, GSK3a/b, IkB‐α, ERK1/2, p38‐MAPK, and intracellular calcium ion mobilization, remained stable over the entire range of passages P5‐P30. Due to these stable characteristics in a wide range of cell culture passages, MG‐63 cells can be considered as a suitable in vitro model to analyze the biocompatibility and biofunctionality of implant materials.